Synaptic remodeling revealed by repeated in vivo observations and electron microscopy of identified frog neuromuscular junctions - Ko, CP (J Neurosci, 1996)
This work aimed to examine the mechanism of synaptic remodeling using repeated in vivo observations, followed by electron microscopy, of identified frog neuromuscular junctions (NMJs). Our previous light microscopic studies suggested that extension of synaptic extracellular matrix (ECM) precedes, and may play a role in, nerve terminal (NT) growth during synaptic remodeling. To test this hypothesis, sartorius muscles were double labeled with a fluorescent dye, 4-(4-diethylamino- styryl)-N-methylpyridinium iodide, for NTs and rhodamine-conjugated peanut agglutinin for synaptic ECM. The double-labeled NMJs were observed in vivo with video-enhanced fluorescence microscopy. Two to three months after nerve sprouting was induced by a nerve graft, the same NMJs were restained and reexamined. After the final in vivo observations, the same NMJs were examined with semiserial thin section electron microscopy. Light microscopic observation of NMJs that showed synaptic ECM longer than the NT was confirmed with electron microscopy. At junctional branches where synaptic ECM extended beyond the NT, a Schwann cell process longer than the NT was observed in one example, whereas a Schwann cell with the same length as the NT was seen in other examples. In both cases, junctional folds were absent at the extended ECM region. In contrast, junctional folds were observed at the region vacated by a retracted NT. These results suggest that extension of synaptic ECM and Schwann cell processes may lead, and play a role in, the NT growth during the remodeling of adult synaptic connections.